TaqMan Real-Time Reverse Transcription-PCR and JDVp26 Antigen Capture Enzyme-Linked Immunosorbent Assay To Quantify Jembrana Disease Virus Load during the Acute Phase of In Vivo Infection - Stewart, Meredith (American Society for Microbiology, 2005)
Jembrana disease virus (JDV) is an acutely pathogenic lentivirus that affects Bali cattle in Indonesia. The inability to propagate the virus in vitro has made it difficult to quantitate JDV and determine the kinetics of virus replication during the acute phase of the disease process. We report for the first time two techniques that enable quantification of the virus and the use of these techniques to quantify the virus load during the acute phase of the disease process. A one-step JDV pol TaqMan real-time reverse transcription-PCR (RT-PCR) assay was developed for the detection and quantification of JDV RNA in plasma. The limit of detection was 9.8 × 10(2) JDV viral RNA copies over 35 cycles, equivalent to 4.2 × 10(4) JDV genome copies/ml, and a peak virus load of 1.6 × 10(12) during the acute febrile period. An antigen capture enzyme-linked immunosorbent assay (ELISA) was also developed to quantify the levels of JDV capsid (JDVp26) over a linear range of 10 to 200 ng/ml. Viral RNA and JDVp26 levels were correlated in 48 plasma samples obtained from experimentally infected cattle. A significant positive correlation (R = 0.860 and r(2) = 0.740) was observed between the two techniques within the range of their detection limits. The relatively insensitive capture ELISA provides an economical and feasible method for monitoring of virus in the absence of more sensitive techniques.